A KONSEP KHALIFAH DAN AMANAH DALAM PENGELOLAAN LINGKUNGAN HIDUP PERSPEKTIF AL-QUR’AN: Pendahuluan, metode penelitian, hasil penelitian dan pembahasan, kesimpulan - la Nirotul Fikri; A’vi Amelia; Zulhannan; Ali Murtadho; Baharudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the concept of khalifah (vicegerent) and amanah (trust) in the Qur’an as the theological foundation for human responsibility in managing and preserving the natural environment. The current ecological crisis reflects human failure to fulfill their divine duty as the stewards of the earth. Using a qualitative approach through library research, this study analyzes Qur’anic verses related to environmental ethics, including Surah Al-Baqarah [2]:30, Al-An‘am [6]:165, Al-A‘raf [7]:56, Ar-Rum [30]:41, and Al-Ahzab [33]:72. Data were obtained from classical and contemporary exegeses, as well as relevant journal articles. The findings indicate that Islam places humans as trustees of Allah to maintain balance (mizan) and prosperity on earth, emphasizing moral, spiritual, and social values in environmental management. The study concludes that by internalizing the Qur’anic concepts of khalifah and amanah, Muslims can develop ecological awareness and environmental ethics rooted in faith, thus contributing to sustainable development based on spiritual values.Keywords: Khalifah, Amanah, Environment.